Critical attachment and the marginalization of political opponents in the aftermath of war in Croatia and Serbia - Penić, Sandra (Array, 2009)
Previous research has suggested that the relationship between in-group identification and reactions to moral violations perpetrated by ingroup members depend on the mode of in-group attachment: While in-group glorification is negatively related to group-based guilt for in-group’s past infractions, critical attachment – which is identification without glorification – is positively related to the acknowledgment of in-group's past wrongdoings (Roccas, Klar & Liviatan, 2006). In our own study, based on comparative survey research conducted in post-war societies across former Yugoslavia, this pattern has been replicated among a representative cohort sample in Serbia, but not in Croatia. This observation has then led us to conduct two types of investigations into contextual factors that might account for societal differences. First, a series of indicators based on survey data highlight differences in moral climates and societal belief structures. While political beliefs tend to be organized in a more hegemonic way in Croatia, public polarization and social uncertainty is a widespread phenomenon in the Serbian post-war society. Second, qualitative analyzes of Croatian TV reports on war events, which were either broadcasted or banned, enlighten the processes by which critical voices are silenced or marginalized in the interaction between policymakers, journalists, and their audiences. These findings are interpreted on the background of more systematic information on the impact of political and economic strategies for silencing critical voices in both countries, as well as structural opportunities for collective resistance to censorship. They open new avenues for conceptualizing the contexts of critical attachment, by which we mean those macro-level conditions and meso-level processes that allow highly identified, but critical, ingroup members to express their views, receive at least minimal recognition, gather, mobilize other group members, and eventually institutionalize a consistent minority voice.